A summary of oil and gas exploration in the Great Australian Bight with particular reference to southern bluefin tuna. (November 2018) - Evans, Karen; McCauley, Robert D.; Eveson, Paige; Patterson, Toby
Abstract: Large numbers of juvenile southern bluefin tuna (SBT; Thunnus maccoyii ) migrate into the warm shelf waters of the Great Australian Bight (GAB) each austral summer. Whilst in the GAB, they are the focus of a commercially important Australian fishery. Recent expansion of activities associated with oil and gas exploration in the GAB over the last five years has raised concerns that noise associated with geophysical surveys and exploratory drilling activities may impact on the migration and behaviour of SBT, with potential flow-on effects on the commercial fishery and current monitoring of the population for management purposes. As a first step in identifying the potential impacts of expansion of oil and gas exploration activities in the GAB on SBT, we establish the historical extent of these activities in the GAB with a primary focus on geophysical surveys. Potential overlap with the distribution of juvenile SBT in the GAB determined from an archival tag dataset (1998–2011) was then explored. Geophysical surveys have occurred throughout the vast majority of the region since 1960, with the size of energy sources used in surveys and the extent of areas surveyed increasing through time. The use of more complex, higher density 3D surveys has increased gradually since 2000. The timing and distribution of exploration activity has had varying degrees of overlap with SBT occurrence and distribution as described by tagged fish. Determining robust measures of the responses to surveys however, is difficult due to a paucity of data on the hearing capabilities of SBT, uncertainties in the true extent of spatial overlap of activities and tagged fish resulting from geolocation methods used for position estimation from archival tag data, complexities in the drivers of behaviour in SBT, and limitations with using observational data to determine cause-and-effect relationships. These difficulties are typical not just of SBT and the GAB region, but apply to investigations of the responses of marine animals to geophysical surveys more broadly. The data presented in this study, however, represent a first step towards understanding oil and gas exploration within a defined region of the Australian marine environment, and provide important context for exploring the potential impact of such activities on a commercially important top order predator of the GAB ecosystem.